Investigasi Sifat Bahan Bakar Campuran Disel Minyak Bumi dan Biodisel Dari Minyak Kelapa Sawit, Minyak Jarak dan Minyak Kanola - S.I Heriyanti; Sumbogo Murti S.D; Adiarso Adiarso (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Biodiesel is a renewable fuel derived from various biomass which is very abundant in Indonesia. The physical properties of biodiesel are similar to those of petroleum diesel, but the fuel significantly reduces green house gas emission and toxic air pollutants. However, there are some disadvantages of biodiesel such as vulnerable to water contamination, lower energy content as well as having problems at low temperatures. Biodiesel can be blended and used in many different concentrations. Indonesia government has launched a policy of biodiesel mix gradually to 30% in 2020. To ensure that policy implementation, a study of blending biodiesel from Palm oil, Jatropha oil and Canola oil has been carried out with various compositions. Some thermophysical properties of the mixture have been investigated in accordance to ASTM standard. The measurement result of biodiesel blends fuel varies according to the mixture composition and origin of biodiesel. Generally, the properties of Palm oil and Canola oil biodiesel blend fuel can meet the standards that apply in Indonesia but biodiesel from Jatropha oil cannot meet the quality standards for oxidation stability. Antioxidant can be used to improve the oxidation stability of biodiesel and its mixture.